Avaliação dos impactos do Programa Uma Terra e Duas Águas (P1+2) sobre a qualidade de vida e a sustentabilidade ambiental de beneficiários do semiárido cearense - Oliveira, Aline de Carvalho (2023)
Living in the semiarid region implies the use of practices that ensure water availability during periods of scarcity. Social policies aimed at improving income and access to water during drought seasons have contributed to coping with dry periods. One of these policies involves the construction of cisterns through the “Um Milhão de Cisternas” Program (P1MC) and the “Uma Terra e Duas Águas” Program (P1+2). To understand the effects of these programs, this study aims to assess the impacts of P1+2 on the quality of life and environmental sustainability of beneficiaries compared to non-beneficiaries. The study was conducted in the municipalities of Canindé and Itapiúna, in the state of Ceará, Brazil, and data were obtained through questionnaires applied to P1+2 beneficiaries and non-beneficiaries. Based on the data, the Quality of Life Index (QLI) and the Environmental Sustainability Index (ESI) were calculated for both groups. The QLI of beneficiaries was lower than that of non-beneficiaries, suggesting a need for greater support and possible adjustments for P1+2 beneficiaries. The ESI was higher for beneficiaries, indicating some positive effect of the program on environmental sustainability. However, the low ESI for beneficiaries highlights vulnerabilities in the context of water security in the semiarid region. This study aims to contribute to the improvement of P1+2, enhancing the quality of life of the population and promoting environmental sustainability.